2021
DOI: 10.1590/1980-549720210009.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Increasing trends in obesity prevalence from 2013 to 2019 and associated factors in Brazil

Abstract: Objective: To investigate the variation of anthropometric indicators from 2013 to 2019 and the factors associated with obesity in Brazil, using information from the National Health Survey. Methods: Cross-sectional study with cluster sampling and simple random sampling in the three stages. Measurements of weight and height among participants in 2013 (n=59,592) and in 2019 (n=6,672) were used. Differences in obesity prevalence were tested by Student’s t test for independent samples. To identify the sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 36 publications
2
21
1
1
Order By: Relevance
“…A nutritional transition involves behavioral, geographic, cultural, and socioeconomic factors. Thus, regional differences must be considered and analyzed individually [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A nutritional transition involves behavioral, geographic, cultural, and socioeconomic factors. Thus, regional differences must be considered and analyzed individually [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Both sexes were associated with obesity, age, and marital status. Regarding education level, it was directly associated among men and inversely associated among women [19].…”
Section: Time Trend Of Obesity Prevalencementioning
confidence: 95%
“…By investigating the variation of anthropometric indicators from 2013 to 2019, as well as the factors associated with obesity in Brazil, using information from the National Health Survey, Ferreira et al [19] estimated a significant increase in obesity prevalence, from 20.8 to 25.9%. They found that the greatest variations occurred in males of the 40 to 59 age group (9.1%).…”
Section: Time Trend Of Obesity Prevalencementioning
confidence: 99%
“…Recently, a national epidemiological survey showed a significant increase in the obesity rate from 20.8% in 2013 to 25.9% in 2019, with further rises between genders [14]. The more considerable increases were found in the 40-59 age group and the median income category for men.…”
Section: The Historical Context Of the Nutrition Transition In Brazilmentioning
confidence: 99%
“…The more considerable increases were found in the 40-59 age group and the median income category for men. On the other hand, the highest increases were found among non-white women with low education [14]. In addition, recent data for 2020 demonstrated that the total costs of obesity in Brazil ranged from USD 133.8 million to USD 6.3 billion per year, varying from direct costs with healthcare and indirect costs in lower productivity and well-being [15].…”
Section: The Historical Context Of the Nutrition Transition In Brazilmentioning
confidence: 99%